Job Satisfaction in Teachers of Autistic Children - Ruminta Simamora (International Journal of Multidisciplinary Sciences and Arts, 2025)
The purpose of the study was to obtain an overview of job satisfaction for teachers of autistic children, to find out the factors of job satisfaction for teachers of autistic children, and to find out the efforts that have been made by a teacher of autistic children in carrying out their profession. This study is qualitative and uses in-depth interviews with three teachers who teach at special needs schools (SLB-C) and handle autistic children. The research period began in January 2025 to April 2025. The results of the study showed that job satisfaction is not obtained from the type of work but how the work is loved and carried out by the worker (teacher). The three subjects in this study felt job satisfaction as teachers of autistic children because they first love children, accept their limitations, do their work affectively and optimally. Good cooperation and assertive communication between fellow teachers, parents, and the school produce positive energy that creates enthusiasm for work. The emotional bond with students is a strength and motivation for teachers to continue to develop teaching methods for the progress of children. The results of the study showed that the three subjects got job satisfaction as teachers of autistic children and by dedicating themselves to children it was felt as a blessing in their work. The limitations of the child create empathy in the parents and together provide education and coaching according to the needs and abilities of the child. Work discipline and the desire to achieve are solely aimed at advancing the child and the school. The school's bias towards teachers is a motivation to be actively involved in tasks and support school programs.